2011
DOI: 10.1159/000327542
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Omphalocele and Polyhydramnios: A Study of 52 Cases

Abstract: Introduction: Unlike gastroschisis, congenital omphalocele is often associated with other anomalies and is frequently complicated by polyhydramnios. We examined the relationships between polyhydramnios, pregnancy outcome and fetal prognosis.Patients and Methods: Clinical data from cases diagnosed antenatally with congenital omphalocele from 1993 to 2006 were analyzed retrospectively. Results: Fifty-two cases were diagnosed antenatally with congenital omphalocele, and 38 of these pregnancies resulted in deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…Along with polyhydramnios, special attention should be paid to the ultrasound examination of the fetus. This was observed by Ozawa et al [100] in a study involving the analysis of 52 fetuses. A quarter of them had trisomy (13 cases, 25%), particularly high rates of Edwards syndrome detected in 10 cases, while Patau syndrome in 2 cases and trisomy 21 in 1 case [100].…”
Section: Gastroschisissupporting
confidence: 58%
“…Along with polyhydramnios, special attention should be paid to the ultrasound examination of the fetus. This was observed by Ozawa et al [100] in a study involving the analysis of 52 fetuses. A quarter of them had trisomy (13 cases, 25%), particularly high rates of Edwards syndrome detected in 10 cases, while Patau syndrome in 2 cases and trisomy 21 in 1 case [100].…”
Section: Gastroschisissupporting
confidence: 58%
“…Ozawa et al [14] examined whether in fetuses with exomphalos, polyhydramnios is an additional predictor for adverse outcome. In their study, polyhydramnios was found in about a third of the cases, and all pregnancies were complicated by additional anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that fetal omphalocele had high rate of associated anomalies when polyhydramnios was detected. 14 For example, Beckwith‐Wiedemann syndrome also shows omphalocele and polyhydramnios prenatally. In those cases, measuring the CHA by 3D ultrasonography to appreciate a coat‐hanger appearance of ribs can be helpful for differential prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 99%